Acute liver failure induced by carbamazepine. Issue 3 (March 1990) - Hadzić, N; Portmann, B; Davies, E T; Mowat, A P; Mieli-Vergani, G
Abstract : Two children developed acute liver failure while taking carbamazepine. Clinical and laboratory findings suggested an immunoallergic reaction, but only one child improved on steroids. Determination of liver function during the first few weeks of treatment and early detection of signs of idiosyncrasy may prevent this rare but severe complication.